2021
DOI: 10.14202/vetworld.2021.113-119
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and parasitological identification of Trypanosoma evansi infecting cattle in South Sulawesi, Indonesia

Abstract: Background and Aim: Sulawesi is an Indonesian island located within the Wallacea region that contains a distinctive mix of Asian and Australasian species. This distinctiveness extends to parasites, including Trypanosoma evansi, the cause of surra. Surra has non-specific clinical signs such as anemia, anorexia, weight loss, drop in milk production, and reproductive disorders which cause economic losses. Due to the trade of livestock, surra has spread in Indonesia from one island to another. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In contrast, T. evansi has long been known to be an important veterinary infection and of all the pathogenic Trypanosoma spp. has the widest geographical distribution, from Africa to South America, Asia, Indonesia and the Philippines [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, T. evansi has long been known to be an important veterinary infection and of all the pathogenic Trypanosoma spp. has the widest geographical distribution, from Africa to South America, Asia, Indonesia and the Philippines [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different results from Egypt have reported that no infection was detected in donkeys and horses; however, surra disease was recorded in camels, with a 31.4% prevalence rate [28]. In South Sulawesi, Indonesia, the prevalence rate of surra was 0% when detected using the conventional parasitological method; however, a 3% prevalence rate was detected in cattle using PCR as a molecular diagnostic method [3]. Therefore, a PCR method using more sensitive primers is required for early diagnostic testing.…”
Section: Discussionmentioning
confidence: 80%
“…Zangooie et al [14] reported zero positive results with microscopic examination of 113 blood samples, whereas seven samples were positive with a PCR method. A similar study in Indonesia [3] found only one positive sample out of 100 blood samples using the blood smear method.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite this disease was endemic in the 1990s in China, affecting animals like buffaloes, cattle, camels and dogs, there are few epidemiological studies conducted on this subject in the past decade (Zheng et al, 2019). "Surra" presents non-specific clinical signs such as weight loss, anorexia, anemia, drop in milk production and reproductive disorders, impacting on economic business (Setiawan et al, 2021). Although this parasite can affect most of the mammals, human infection is rare (Desquesnes et al, 2013;Wabale et al, 2015).…”
Section: Introductionmentioning
confidence: 99%